Spectrophotometric Study of Ni(II)-Glycinamide Complex Formation - Tajodini, Niloufar; Moghimi, Ali (Asian Journal of Chemistry, 2011)
The formation constants of Ni(II)-glycinamide system were determined in buffer solution, pH = 4.0 (I = 0.4 mol L-1 in NaClO4 at 10, 15, 20, 25, 30 ºC) using UV-visible spectrophotometric method. The optical absorption spectra of Ni(II)-glycinamide system were analyzed in order to obtain formation constants and stoichiometries based on SQUAD software. Determining the formation constants at various temperatures enabled us to calculate some thermodynamic parameters as K, DGº, DHº and DSº related to the nickel(II) glycinamide complexes.